APPLICATION OF PROJECT MANAGEMENT IN ELEVATOR CONTROL KHARKIV - and and (Municipal economy of cities. Series: «Economy science», 2013)
Provided the use of project management for the Elevator Control of the city, is a classification of projects and the life cycle of the proposed project.